GİRİŞİMCİLERİN KULLANDIĞI ESNAF VE SANATKÂRLAR KREDİ VE KEFALET KOOPERATİFİ KREDİLERİNİN GÖRÜNÜMÜ: ELAZIĞ İLİ İNCELEMESİ - SAYINER, ERDAL (Fırat Üniveristesi, 2019)
Girişimci emek, sermaye ve doğal kaynağı bir araya getirerek menfaat elde etmek için risk alan kişidir. Bireylerin dolayısıyla toplumların refah seviyesi arttıran girişimcilik, devletlerin ekonomik gelişmelerinde, firmaların uluslararası alanda rekabet edebilmelerinde başvurabilecekleri en önemli yöntemdir. Esnaf ve sanatkâr ise bedeni ve sermayesi ile mikro ölçekte üretim yâda ticaret yapan kişi olarak ifade edilebilir. Türkiye ekonomisinde ve istihdamında önemli paya sahip olan esnaf ve sanatkâr, aynı zamanda girişimcilerin büyük çoğunluğunun ekonomik birime dönüştüklerinde içine dâhil olduğu grubu da ifade eder. Tez çalışmasında Girişimcilerin Kullandığı Esnaf ve Sanatkârlar Kredi ve Kefalet Kooperatifi Kredilerinin Görünümü Elazığ İli Özelinde İncelenmiş, artması için önermelerde bulunulmuştur. Anahtar Kelimeler: Esnaf ve Sanatkârlar Kredi ve Kefalet Kooperatifi Kredileri, Girişimcilik.

Entrepreneur is a person who takes risks to bring benefits by bringing together labor, capital and natural resources. Entrepreneurship, which increases the welfare level of individuals and societies, is the most important method that can be applied in the economic development of the states and the competitiveness of firms in the international arena. Tradesmen and craftsmen can be expressed as people who produce or trade on a micro scale with their body and capital. artisans and craftsmen who have a significant share in Turkey's economy and employment, but also refers to the group of entrepreneurs when they return to economic units to be incorporated into the majority. In the thesis, the view of the loans of the Tradesmen and Craftsmen Credit and Surety Cooperative Used by Entrepreneurs was examined in Elazığ Province and suggestions were made to increase it. Keywords: Tradesmen and Craftsmen Credits and Bail Cooperative Loans, Entrepreneurship.
The effect of Tradesmen and Craftsmen Credit and Surety Cooperative Loans on Entrepreneurship: A review of Elazığ province
Keywords: İşletme